Pengaruh Faktor-faktor Kualitas Pelayanan Terhadap Kepuasan Nasabah di Bank Syariah Indonesia (BSI) KCP Solo Urip Sumoharjo - Fatahillah; Muhammad Tho’in; Sumadi (ITB AAS INDONESIA Surakarta, 2026)
This study aims to analyze the effect of service quality dimensions, namely tangible, reliability, responsiveness, assurance, and empathy, on customer satisfaction at Bank Syariah Indonesia (BSI) KCP Solo Urip Sumoharjo. The study employed a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 80 customers selected using a simple random sampling technique. Data analysis was conducted using multiple linear regression, t-test, F-test, and coefficient of determination (R²) with the assistance of SPSS software. The results indicate that service quality simultaneously has a positive and significant effect on customer satisfaction. Partially, all service quality dimensions, including tangible, reliability, responsiveness, assurance, and empathy, have a positive and significant effect on customer satisfaction. Among these dimensions, reliability is the most dominant factor influencing customer satisfaction. The coefficient of determination (R²) of 0.675 indicates that 67.5% of customer satisfaction can be explained by service quality variables, while the remaining 32.5% is influenced by other factors outside the research model. These findings suggest that improving service quality is essential for enhancing customer satisfaction in Islamic banking institutions.